Determine the Radon Gas Level Using the GIS Technique for Baghdad City - Hassan, Mustafa Ali; Ibrahim, Ola Adil (Iraqi Journal of Science, 2018)
In this work, radon concentrations in the polluted environment were measured within the Baghdad sample surface soil conservation, and this was done using a RAD-7 mobile detector. The work consists of four parts:The first part includes calculating the latitude and longitude of each point of the study area using the Global Positioning System (GPS). The second part of which includes Determination of 222Rn gas concentrations in surface soil samples. In the northeast part of Baghdad, the highest concentration of radon was found in Al-Shaab area (3.11 ±175.33 Bq / m3), while the lowest gas concentration in AL Gzeera area (6.67±73.00 Bq/ m3), In the northwest part of Baghdad, the highest concentration of radon was found in the al-Taji area (4.22 ± 179.33Bq / m3) and the lowest concentration of Radon gas in Al Ghazaliya area (3.11 ± 68.33 Bq/ m3). Inthe southeast part of Baghdad, the highest concentration of radon was found in ALWahda area (1.78 ±175. 33Bq / m3) while the lowest rate of radon gas is located inthe Karada area (1.78 ± 41.67Bq / m3). The highest concentration of radon gas can be observed in the southwest part of Baghdad in Mahmudiya area (4.22 ±185.67Bq/m3), while the lowest concentration of radon in Aamiriya (2.22 ± 78.67Bq/m3). The third part includes the applied the techniques of interpolation using the radon data available in the known sites to estimate the radon data for the non-measured area, which will help to develop an effective plan to reduce the concentration of radon in the study area. The fourth part includes the preparation of a soil surface classification map in all selected areas where the soil was classified into five species using the Erdas2014.